Toward Nurses' Transformative Agency in Transitional Care for Older Adults: A Change-Laboratory Intervention - Rikke B Bøje; Peter Musaeus; Dorthe Sørensen; Mette S Ludvigsen (SAGE Publishing, 2022)
Mobilization of nurses' agency across healthcare sectors is needed to counter challenges associated with older adults' transitions between hospital and primary care. Based on Cultural Historical Activity theory and the Change Laboratory method, we developed a learning intervention with 16 nurses. The aim was to foster the nurses' transformative agency to improve care. Video-recording of nine learning sessions were transcribed and analyzed. Results demonstrated that shared transformative agency exhibited as an emergent phenomenon crossing sectoral boundaries as a prerequisite for change in transitional care. The nurses progressed from acting as individuals criticizing the current conditions to collectively forming a vision around a transitional care model. This was nurtured through the nurses' negotiations which included a recognition of sharing similar challenges deriving from the healthcare organization and related financial restrictions, and conflicting healthcare and nursing ideals across healthcare sectors. The evolution of transformative agency was grounded in a professional nursing identity.